TRAINING TEXTILE KNOWLEDGE SUPPLY CHAIN BASED SERVICE “PRAKTIS” IN SOUTH OF JAKARTA - Mawardi, Tatang Khalid; Dwitarwasto, Toto; Pithaloka, Hanna (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
With a strong domestic market demand, in textile and clothing manufacturing centers in Indonesia. Micro, Small, and Medium Enterprises (MSMEs) play a very significant role. Despite all of the limitations, MSMEs are unable to use the supply chain management that large-scale businesses do, and their operations are frequently unpredictable. Therefore, the availability of supply chain-based services provides MSMEs with helpful solutions to their difficulties. The goal of knowledge textile training is to support MSMEs in growing their businesses by providing training to Supply Chain service named Praktis located in South of Jakarta starting September until November 2023 to 22 participants from different divisions such as sales, procurement and merchandiser who are dealing directly to MSMES actors. The program consists of discovery learning, sharing experience and discussion. The result participants trained were enthusiastic and the training textile knowledge were targeted to empower service more efficient. The training received a rating 4,78/5 and the level of understanding of respondents achieved to 95,6 %.